Against struggle and hustle: form of the queer travel narrative in Kate O'Brien's Farewell Spain. Issue 3 (2nd September 2021) - Faragher, Megan
ABSTRACT: The interwar was a period of emergent travel narratives by women, though masculinity still permeated the genre: books like Isherwood and Auden's Journey to a War (1939) or Evelyn Waugh's Waugh in Abyssinia (1936) were met by books like Rebecca West's Black Lamb and Grey Falcon (1941), as increasingly mobile women writers met men in a field from which they had been excluded. The self-othering of the travel experience also enabled new ways of allegorizing the experiences of otherness experienced by queer writers amidst social and political repression. This essay argues Kate O'Brien, the author of Farewell Spain (1937), wields the form of a collaborative travel narrative to challenge heteronormative patriarchy's control over both queer bodies and identities, but also to inspire new forms of political engagement. While so much of interwar prose was motivated by political commitment and activism, in Farewell Spain O'Brien advocates for an alternative form of political intervention distinct from the "struggle and hustle" promoted by the era's most prolific writers, aligning instead with a philosophy of pleasure and "easy" to counter the rhetorical. Farewell Spain presents us with a queer approach to the travel narrative that bolsters and embodies anti-fascism, even if the methods themselves are, purposefully and self-consciously, nonproductive.